Tahlīl Riwāyah Salāmullāh ‘Ala ‘Ainaik li Muhammad al-Muslim (Dirāsah Simiyāiyyah Roland Barthes) - Diah Ayu Khoirunnisa; Moh. Zawawi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The aims of this study are: 1) to describe the meaning of denotation and connotation and the novel Salamullahi 'Ala Ainik; 2) knowing the message contained in the novel Salamullahi 'Ala Ainik. This research is descriptive qualitative research, and this research is also a type of library research because it is based on documents in the form of literature books, journals, and other data sources in the library. In collecting data, the researchers used reading and note-taking techniques. And the data analysis techniques used by researchers in this study are data reduction, data presentation, analysis, and drawing conclusions. The results of this study are: 1) the novel has 25 denotative signs and 25 connotative signs in the main character's conversation (Ghussan); 2) has 25 messages contained in the conversation of the main character (Ghussan), which is the intent of denotative and connotative meanings